2016
DOI: 10.20431/2347-3134.0410005
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of Optimizing Whatsapp as an Instructional Tool for Teaching EFL Writing in Indonesian Senior High Schools

Abstract: The typical characteristics of adolescent learners challenge teachers to find strategies to engage them. One of the strategies is through mobile learning. This paper shares three techniques of writing activities to help adolescent learners develop their text types writing ability using WhatsApp. The techniques are brainstorminggroup drafting-teacher's feedback, starterquick writingpeer feedback, and information gatheringelaboration exerciseschecklist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…In terms of the format of providing and exchanged e-feedback, this study has found that English language tutors used various online platforms such as Blackboard collaborative tools, Zoom, Microsoft Teams, Email, and WhatsApp for providing efeedback. This finding supports the previous evidence on tutors' mixed preferences of using various formats of online platforms for providing e-feedback [12,29,33,53,54].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of the format of providing and exchanged e-feedback, this study has found that English language tutors used various online platforms such as Blackboard collaborative tools, Zoom, Microsoft Teams, Email, and WhatsApp for providing efeedback. This finding supports the previous evidence on tutors' mixed preferences of using various formats of online platforms for providing e-feedback [12,29,33,53,54].…”
Section: Discussionsupporting
confidence: 90%
“…During the outbreak of the coronavirus pandemic tutors are gradually relying on several supportive digital technologies such Blackboard LMS, WhatsApp, email, Zoom, Microsoft Teams, Google Docs, screencasts, track changes in the word processor to provide their students with e-feedback [12,29,[30][31][32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a handy and friendly-user application, WhatsApp has been preferred to assist language teachers in facilitating the learning process. Its utilization has provided many benefits, especially in enhancing students' English vocabularies (Bensalem, 2018;Hashemifardnia et al, 2018;Jafari & Chalak, 2016), improving their reading and writing skills (Ahmed, 2019;Susanti & Tarmuji, 2016), boosting the students' learning motivation as well as reducing their learning anxiety (Ali & Bin-Hady 2019;Indaryani & Suliworo, 2018), and more importantly, helping teachers deliver instructions (Alshammari, 2017) which are commonly sent in the chat groups feature (Amry, 2014). Due to these potential advantages, WhatsApp chat groups are currently getting more popular among language teachers and educators.…”
Section: Introductionmentioning
confidence: 99%
“…This situation makes WA become more popular to use and this is in line with the data mentioned previously in which 83% internet users in Indonesia actively use WhatsApp on their gadgets. The potential of WA is not only due to its easily downloaded application but also for its flexibility and various features to send text, video, audio, links, documents, location, and pictures (Susanti & Tarmuji, 2016). Some studies have been conducted in the utilization of WA in English language teaching.…”
Section: Introductionmentioning
confidence: 99%